Standard Contract on Banking Sector: Regulation and Description in Internal Banking Regulations - Desak Putu Dewi Kasih; Putu Devi Yustisia Utami (University of Udayana, 2021)
This study aims to determine the regulations regarding standard contracts in the banking sector after the existence of the authority of the Otoritas Jasa keuangan, to find out the legal consequences of violations of the provisions of standard contracts carried out by banking financial services and to determine efforts to prevent violations of standard contracts by banking financial services. This is normative legal research with with statutory approach and a conceptual approach. The results show that the regulation regarding the standard contract after the existence of the OJK as a financial service consumer protection agency is regulated through the Financial Services Authority Regulation (POJK) No.1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector and in the Financial Services Authority Circular Letter (SEOJK) No. 13 /SEOJK.07 / 2014 regarding the Standard contract. The legal consequences of violating the provisions of the standard contract are not regulated in the POJK and the SEOJK. When it compared with the provisions of article 18 paragraph (3) of the Consumer Protection Law which explicitly states that violations of article 18 paragraphs (1) and (2) result in standard clauses being null and void, POJK and SEOJK only require financial service actors to make action plan, hence it is deemed to have no clear legal consequences. One of the efforts that must be made by banking financial service actors to prevent violations of the provisions of the standard contract is by making standard contract regulations independently and elaborating them in the internal banking regulations.